Pengaruh Literasi terhadap Keterampilan Proses Sains Siswa di MI Roudlotul Falah Kecamatan Sidoarjo Kabupaten Sidoarjo - Saidur Ridlo (TABYIN: JURNAL PENDIDIKAN ISLAM, 2019)
Literacy is the ability to access, understand, and use something intelligently through various activities or activities, including reading, seeing, listening, writing and speaking. Science Process Skills (KPS) is a learning approach oriented to science learning. This study aims to study the Effect of Literacy on Science Process Skills of Students at MI Roudlotul Falah District of Sidoarjo, Sidoarjo Regency. This type of research is a quantitative approach. The type of research approach is descriptive quantitative, namely research to give a description of the symptoms, phenomena, or facts examined by describing the value of independent variables, without intending to connect or compare. Data collection methods used in this study were observation, interviews, documentation and questionnaires. From the results of the study, the Influence of Literacy on the development of Science Process Skill Students have a value of 78.190%, thus the variable shows sufficient category. This means demonstrating that Literacy Against the Development of Science Process Skill is quite influential for Students at MI Roudlotul Falah.